Phase transition from quark-gluon plasma to matter after the big bang - Ch, Sodbileg (Scientific transaction of the National University of Mongolia. Physics, 2022)
The dependence of the energy density distribution around a quark and an antiquark as a function of temperature has been studied in this work. Temperature range was 0.7-1.3 times the critical temperature of the phase transition from a hadronic matter to quark gluon plasma. Using Monte Carlo numerical simulation we have found that above the critical temperature wc can observe a quark as a single particle.